Implementation of Restorative Justice in Handling Children in Conflict with the Law in Palembang City (Case Study of Child Rapists) - Annisa Nur Aziza; Umar Anwar; Budi Priyatmono; Ali Muhammad (Indonesian Journal of Social Science Education (IJSSE), 2026)
The implementation of restorative justice in Indonesia is legally regulated under the Juvenile Criminal Justice System Law. However, it faces challenges, particularly in serious crimes such as the rape of a minor at the Kuburan Cina cemetery in Palembang, involving four juvenile offenders. One of them, IS (aged 16), was sentenced to ten years in LPKA, while the other three, all under 12, were placed in LPKS for one year of rehabilitation. This study critically examines the application of restorative justice in cases of child-perpetrated sexual violence, focusing on the balance between offender rehabilitation and justice for victims. Using a qualitative case study method, data were obtained through interviews with legal authorities, social workers, families, and community figures. The findings reveal that restorative justice efforts are insufficient in achieving reconciliation, with communities—especially victims’ families rejecting such approaches in serious offenses. The perceived leniency has fueled public preference for retributive justice.